Islamic Educational Values in Customary Tradition: Symbolic Contestation of the Nemat Kaji Tradition in Malin Deman - Dedy Novriadi; Nilda Susilawati; Syubli Syubli; Fathudin Aziz Al Hanif (Madania: Jurnal Kajian Keislaman, 2025)
This study aims to analyze the contestation between substantive Islamic educational values and symbolic ceremonial practices in the Nemat Kaji tradition, a traditional wedding procession of the Malin Deman community in Mukomuko Regency, which represents a fusion of local culture and Islamic symbols. Through a qualitative approach using participatory observation techniques, in-depth interviews, and literature studies, this study found that although the Nemat Kaji tradition upholds Islamic educational values in the aspects of faith, worship, and morals, there is a shift in meaning between generations. The older generation tends to maintain the spiritual meaning of religious symbols, while some of the younger generation sees them as formalistic customary obligations. The role of religious scholars is also divided between maintaining customary forms and encouraging the reform of religious symbols. This study concludes that the Nemat Kaji tradition is at the intersection of cultural preservation and the revitalization of Islamic values, which demands a more reflective and contextual approach to Islamic education. These findings provide theoretical contributions to the development of studies on local culture-based Islamic education and enrich the discourse on the dynamic relationship between custom and religion in the context of Indonesian Muslim society. Penelitian ini bertujuan untuk menganalisis kontestasi antara nilai-nilai pendidikan Islam yang bersifat substantif dengan praktik simbolik seremonial dalam tradisi Nemat Kaji dalam prosesi adat pernikahan masyarakat Malin Deman, Kabupaten Mukomuko, yang mempresentasikan perpaduan antara budaya lokal dan simbol-simbol keislaman. Melalui pendekatan kualitatif dengan teknik observasi partisipatif, wawancara mendalam, dan studi pustaka, penelitian ini menemukan bahwa meskipun tradisi Nemat Kaji menyimpan nilai-nilai pendidikan Islam dalam aspek akidah, ibadah, dan akhlak, terjadi pergeseran makna antar generasi. Generasi tua cenderung mempertahankan makna spiritual simbol-simbol religius, sedangkan sebagian generasi muda melihatnya sebagai kewajiban adat yang bersifat formalistik. Peran ulama pun terbagi antara mempertahankan bentuk adat dan mendorong reformasi simbol keagamaan. Penelitian ini menyimpulkan bahwa tradisi Nemat Kaji berada pada titik persilangan antara pelestarian budaya dan revitalisasi nilai Islam, yang menuntut pendekatan pendidikan Islam yang lebih reflektif dan kontekstual. Temuan ini berkontribusi secara teoretis bagi pengembangan pendidikan Islam berbasis budaya lokal serta memperkaya diskursus tentang relasi dinamis antara tradisi dan agama dalam konteks masyarakat muslim Indonesia.